Correction: Alfei, S.; Zuccari, G. Recommendations to Synthetize Old and New β-Lactamases Inhibitors: A Review to Encourage Further Production. Pharmaceuticals 2022, 15, 384 - Silvana Alfei; Guendalina Zuccari (MDPI AG, 2022)
In the original publication [...]